IMPLEMENTASI PENDIDIKAN KRISTEN BERDASARKAN AMSAL 3 DI ANTARA MAHASISWA SEKOLAH TINGGI TEOLOGI DI SURABAYA - Suryaningsih Soepardi (Jurnal Excelsior Pendidikan, 2020)
Abstract: Christian education is education based on the Word of God. The objectives of this study were: (1) To find out to what extent the tendency of the implementation of Christian education based on Proverbs 3 among the students of the Theology College in Surabaya. (2) To find out which dimension is dominant for the implementation of Christian Education based on Proverbs 3 among Students of Theological College in Surabaya. (2) Finding out which background is dominant in the implementation of Christian Education based on Proverbs 3 among Theological College Students in Surabaya. This study uses an explanatory-confirmatory approach. The research subjects were all students of the Theological College in Surabaya with a total of 60 students. The technique of taking the population uses "Disproposionate Stratified Random Sampling" which means, using a study of the entire population. Data collection using a Likert questionnaire. The calculation of the questionnaire used the SPSS 19 program. The results of the study were: (1) Hypothesis 1 Tendency of the Implementation of Christian Education based on Proverbs 3 among Students of Theological College in Surabaya in Low to Medium Positions. (2) Hypothesis Testing H2, it is assumed that the dominant dimension in determining the implementation of Christian education based on Proverbs 3 among students of the Theology College in Surabaya is the dimension of honest life. (3) Hypothesis Test 3 Background The dominant background category is the Background Status of Family Origin.Abstrak: Pendidikan Kristen adalah pendidikan berdasarkan Firman Tuhan. Tujuan penelitian ini adalah: (1) Untuk mengetahui sejauh mana kecenderungan pelaksanaan pendidikan Kristen berbasis Amsal 3 pada mahasiswa Sekolah Tinggi Teologi di Surabaya. (2) Untuk mengetahui dimensi mana yang dominan dalam penyelenggaraan Pendidikan Kristen Berbasis Amsal 3 pada Mahasiswa Sekolah Tinggi Teologi di Surabaya. (2) Mengetahui latar belakang mana yang dominan dalam penyelenggaraan Pendidikan Kristen berdasarkan Amsal 3 pada Mahasiswa Teologi di Surabaya. Penelitian ini menggunakan pendekatan eksplanatori-konfirmatori. Subjek penelitian adalah seluruh mahasiswa Sekolah Tinggi Teologi di Surabaya yang berjumlah 60 siswa. Teknik pengambilan populasi menggunakan â€œDisproposionate Stratified Random Samplingâ€ yang artinya menggunakan studi terhadap seluruh populasi. Pengumpulan data menggunakan kuesioner likert. Perhitungan kuisioner menggunakan program SPSS 19. Hasil penelitian ini adalah: (1) Hipotesis 1 Kecenderungan Pelaksanaan Pendidikan Kristen Berbasis Amsal 3 Pada Mahasiswa Sekolah Tinggi Teologi di Surabaya pada Posisi Rendah Menengah. (2) Pengujian Hipotesis H2, diasumsikan bahwa dimensi yang dominan dalam menentukan penyelenggaraan pendidikan Kristen berbasis Amsal 3 pada mahasiswa Sekolah Tinggi Teologi di Surabaya adalah dimensi kehidupan jujur. (3) Uji Hipotesis 3 Latar Belakang Kategori latar belakang yang dominan adalah Status Latar Belakang Asal Keluarga.